AFFIRMING MORAL EXCELLENCE: STRENGTHENING CHARACTER EDUCATION THROUGH HABITUATION AND INNOVATIVE LEARNING MANAGEMENT - Widat, Faizatul; Wulandari, Aning Suci (Universitas Nurul Jadid, 2023)
This study investigates the positive impact of the management of strengthening moral character education through habituation programs and educational learning in early childhood on their moral development. This approach is designed to reinforce noble values and ethics in children's daily lives at an early stage of development. The research site was conducted at Al Munir Kalianget Islamic Kindergarten Banyuglugur Situbondo. The research methodology uses a qualitative research approach of the case study type involving the implementation of the Habituation Program specifically designed to improve the understanding and application of moral values. Data was collected through observations, interviews, and questionnaires given to teachers and parents of children involved in the program. The results showed a significant improvement in early childhood children's understanding and moral behaviour after participating in the Habituation Program and educational learning. The collaboration between the school environment and the family proves its effectiveness in forming a strong character and high morale in children. This finding has important implications in the context of early childhood character education. It highlights the strategic role of management in strengthening moral character education in shaping the next generation who are qualified, with integrity, and full of responsibility. This research contributes to the practical and theoretical understanding of increasing children's moral excellence through integrated character education interventions.